Online Learning Implementation in English Class at SMP Mutiara Singaraja During Pandemic Covid-19 - Febrin, Sabrina; Agustini, Dewa Ayu Eka; Pratiwi, Ni Putu Astiti (Journal of Educational Study, 2023)
The study aims to describe how the implementation of online English learning with its difficulties and strategies used to deal with those difficulties at SMP Mutiara Singaraja. Researcher used descriptive qualitative research design. There was a total of twenty-seven participants, on SMP Mutiara Singaraja. Observation sheets, questionnaires, and interviews were used by researcher as data collection instruments. The results showed that the implementation of online learning at SMP Mutiara Singaraja has been conducted properly followed the Ministry of Education and Culture's guidelines, but not strictly. Even though online learning has been running for more than a year, there are still some difficulties experienced by both teachers and students. Fortunately, over the time EFL teachers and students had found their own strategies to deal with those difficulties, so they can conduct the online learning effectively.